Modeling household's willingness to pay for sustainable rural drinking water supply using hand-pumped boreholes: a bivariate probit analysis in Chilga District, Northwestern Ethiopia - Nega, Y. M.; Taw, T. B.; Mesele, M. A.; Abebe, M. T. (IWA Publishing, 2025)
Access to safe drinking water remains a critical issue in rural areas of developing countries, including Ethiopia, where many communities rely on unimproved sources. This study assesses households’ willingness to pay (WTP) for improved drinking water services in rural Chilga District, Northwestern Ethiopia, focusing on hand-pumped boreholes as a sustainable solution. Using a contingent valuation method (CVM) with a double-bounded dichotomous choice format and a bivariate probit model, the study identifies key factors influencing WTP. Results reveal that female-headed households are more supportive of water improvement projects, while older respondents and those with higher perceived water quality are less likely to pay. Education significantly increases WTP, and households spending more time collecting water are more inclined to pay for improvements. Marginal effects of income on WTP suggest the need for flexible pricing models. The study underscores the need for targeted interventions, educational campaigns, and flexible bidding strategies to enhance community engagement and ensure equitable access to improved water services.